(3GdJehjd GdeMdj hGdJfejI GdeMdjIs - (3YHO GdeWdH(B, (3YHO GdMejOs ((3GdbGgQI(B:s (3GdOGQ GdLGeYjI(B,s, 2001)
(3GdJfejI GdeMdjI hGdMGLI Gdi GdJehjd GdeMdj, GdebheGJ GdGSGSjI dEOGQI GdJfejI GdeMdjI, GdJehjd GdeMdj aj VhA fXe GdEOGQI GdeMdjI hGdMce GdeMdj, gjcd GdJehjd GdeMdj aj VhA bhGfjf GdEOGQI GdeMdjI aj eUQ , Jehjd GdeTQhYGJ Ydi eSJhi GdeMdjGJ hOhQ GdeTGQcI GdTYHjI, OhQ HYV eDSSGJ GdJehjd aj Jehjd eTQhYGJ GdeMdjGJ , GdehGRfI GdeMdjI hNWhGJ EYOGOGgG hJfajPgG hechfGJgG(B- (3GdENJdGdGJ aj gjcd GdJehjd GdeMdj hSHd YdGLgGs
Keywords: (3GdJehjds; (3GdJfejI GdeMdjIs